2005
DOI: 10.1016/j.cell.2005.05.026
|View full text |Cite
|
Sign up to set email alerts
|

SLAM Family Receptors Distinguish Hematopoietic Stem and Progenitor Cells and Reveal Endothelial Niches for Stem Cells

Abstract: To improve our ability to identify hematopoietic stem cells (HSCs) and their localization in vivo, we compared the gene expression profiles of highly purified HSCs and non-self-renewing multipotent hematopoietic progenitors (MPPs). Cell surface receptors of the SLAM family, including CD150, CD244, and CD48, were differentially expressed among functionally distinct progenitors. HSCs were highly purified as CD150(+)CD244(-)CD48(-) cells while MPPs were CD244(+)CD150(-)CD48(-) and most restricted progenitors were… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

96
2,681
9
22

Year Published

2007
2007
2017
2017

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 2,840 publications
(2,808 citation statements)
references
References 60 publications
96
2,681
9
22
Order By: Relevance
“…Furthermore, Danet et al demonstrated that bone marrow HSCs cultured at 1.5% O 2 promoted their ability to engraft and repopulate the haematopoietic organ of immunocompromised recipient mice 56 . Intriguingly, antibodies against markers that substantially enriched for HSCs during purification identify cells that are localized to the sinusoidal endothelium, as opposed to the more hypoxic endosteal lining 57 . The precise location of bone marrow HSCs remains controversial; however, it is possible that different stem and progenitor cell populations require different O 2 conditions, so that multiple niches characterized by different O 2 levels might exist in bone marrow.…”
Section: O 2 Levels Regulate Hematopoietic and Embryonic Stem Cellsmentioning
confidence: 99%
“…Furthermore, Danet et al demonstrated that bone marrow HSCs cultured at 1.5% O 2 promoted their ability to engraft and repopulate the haematopoietic organ of immunocompromised recipient mice 56 . Intriguingly, antibodies against markers that substantially enriched for HSCs during purification identify cells that are localized to the sinusoidal endothelium, as opposed to the more hypoxic endosteal lining 57 . The precise location of bone marrow HSCs remains controversial; however, it is possible that different stem and progenitor cell populations require different O 2 conditions, so that multiple niches characterized by different O 2 levels might exist in bone marrow.…”
Section: O 2 Levels Regulate Hematopoietic and Embryonic Stem Cellsmentioning
confidence: 99%
“…As stem cells lie in a special niche that nourishes them and keeps them in a primitive state, the high vascularity may contribute to the formation of the niche. In other organs, stem cells seem to be localized in highly vascular areas (24)(25)(26). Indeed, the majority of hematopoietic stem cells in the bone marrow and spleen are in contact with endothelial cells (26).…”
Section: Discussionmentioning
confidence: 99%
“…In other organs, stem cells seem to be localized in highly vascular areas (24)(25)(26). Indeed, the majority of hematopoietic stem cells in the bone marrow and spleen are in contact with endothelial cells (26). The importance of high vascularity to stem cells may reflect their need for nourishment and oxygen delivered through the blood supply.…”
Section: Discussionmentioning
confidence: 99%
“…47 It has been shown that a combination of signaling lymphocyte activation molecule (SLAM) expression defines long-term HSCs (CD150 þ CD48 À CD244 À ) from adult BM using FACS. 48 Because of its limited expression pattern, this combination of SLAMs can also be used in immunofluorescent imaging of LT-HSCs in tissue sections. By using this technique, another HSC niche has been identified in the sinusoidal endothelium.…”
Section: Self-renewal Of Hscsmentioning
confidence: 99%
“…It has been shown that more cells with the LT-HSC phenotype are found attached to the sinusoidal endothelium within the center of BM than to the bone surface. 48 The endothelial cells were initially proposed to act as the niche cells that interact with HSCs in this vascular niche. 43 A subsequent study identified a type of reticular cell that expresses high levels of the chemokine CXCL12 (also known as stromal-derived factor 1, SDF-1) interacting with HSC interacting cells within the sinusoidal vascular niche.…”
Section: Self-renewal Of Hscsmentioning
confidence: 99%